2022
DOI: 10.1371/journal.pone.0270277
|View full text |Cite
|
Sign up to set email alerts
|

Use of an efficient unbiased estimator for finite population mean

Abstract: In this study, we propose an improved unbiased estimator in estimating the finite population mean using a single auxiliary variable and rank of the auxiliary variable by adopting the Hartley-Ross procedure when some parameters of the auxiliary variable are known. Expressions for the bias and mean square error or variance of the estimators are obtained up to the first order of approximation. Four real data sets are used to observe the performances of the estimators and to support the theoretical findings. It tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Hence, estimators are chosen not only for their unbiasedness, but also for how widely their estimates vary from sample to sample [21]. RMSE is a metric that commonly used to evaluate bias and estimation accuracy [21,22]. Our result suggested that BGDM estimator is more accurate and has minimum standard error.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Hence, estimators are chosen not only for their unbiasedness, but also for how widely their estimates vary from sample to sample [21]. RMSE is a metric that commonly used to evaluate bias and estimation accuracy [21,22]. Our result suggested that BGDM estimator is more accurate and has minimum standard error.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, identifying that an estimator is unbiased on mean is not very useful if the values of estimators fluctuate between samples. Hence, estimators are chosen not only for their unbiasedness, but also for how widely their estimates vary from sample to sample [21]. RMSE is a metric that commonly used to evaluate bias and estimation accuracy [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailor and Lone (2014); Mehta and Tailor (2020); Singh and Nigam (2020) and suggested various ratio type estimators for estimation of population mean using different sampling methods. Oncel Cekim & Kadilar (2018); Javed et al (2019); Shabbir and Onyango (2022) and Oncel Cekim (2022) introduced unbiased estimators under various sampling methods.…”
Section: Introductionmentioning
confidence: 99%